Inverse Boundary Value Problem Solution for Deflected Beams Joined Together by Elastic Medium (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we extend the Euler-Bernoulli beam theory for bending boundary value problem into mechanically coupled system. We follow the inverse approach to find the exerted force on two beams separated by elastic material. The theory was utilized in two ways: in the first approach, we calculate the force exerted on the beams using known values for the stiffness constant and measured values for the beam deflections. In the second method, we calculate the stiffness constant using a single known force and measured deflections. These problems are typically illposed problems whose solution does not depend continuously on the boundary data. To minimize the variational functional, we develop an iterative algorithm based on the system of three equations: the direct, adjoint, and control equations. Then, we present numerical examples to obtain the solutions.
Keywords: Euler-Bernoulli beam theory; Inverse problem; Tikhonov regularization; touchscreen; ill-posed; adjoint equation